Performance Evaluation of Urban Drainage Systems Under Sedimentation and Solid Waste Influence - Imanuel Kemenangenta Perangin Angin; Doni Febriawan; Rendy; Jeremia Dinata Perangin Angin (Indonesian Journal of Environment and Sustainability Issues, 2026)
Urban flooding remains a persistent challenge in developing cities, often attributed not only to insufficient drainage capacity but also to operational issues such as sedimentation and solid waste accumulation. This study aims to evaluate the hydraulic performance of an existing urban drainage system and to determine its capacity in accommodating design discharge generated from rainfall and domestic wastewater in a residential area of Pontianak, Indonesia. The research applies integrated hydrological and hydraulic analyses using both primary and secondary data. Field observations were conducted to obtain channel dimensions, sedimentation levels, and existing physical conditions. Meanwhile, secondary data consisted of ten years of maximum daily rainfall records. Rainfall frequency analysis was carried out using the Gumbel distribution, while rainfall intensity was estimated using the Mononobe method. The rational method was then employed to calculate design discharge, which was compared with the existing channel capacity under both ideal and sediment-affected conditions. The findings reveal that the drainage system is hydraulically capable of conveying the design discharge under optimal conditions. However, the effective capacity is significantly reduced due to sediment deposition, solid waste accumulation, structural deterioration, and uneven road surfaces. These factors collectively reduce flow efficiency and contribute to localized flooding. This study highlights that drainage system performance is strongly influenced by maintenance practices and environmental conditions, emphasizing the need for integrated management strategies to achieve sustainable urban flood mitigation.